ANALISIS RASIO LIKUIDITAS, PROFITABILITAS, SOLVABILITAS DAN PERPUTARAN PERSEDIAAN UNTUK MENILAI KINERJA PERUSAHAAN RETAIL YANG TERDAFTAR DI BEI - Masta Sembiring (JURNAL AKUNTANSI BARELANG, 2019)
Measurement of a company's performance can be seen from financial ratio or stock returns. This study aims to know whether liquidity, profitability, solvency, and inventory turnover have an effect after being analyzed on the performance of company on companies listed on Indonesia Stock Exchange. The variables used are Current Ratio, Return on Investment, Debt to Asset Ratio, Inventory Turnover to Net Profit Margin. The population in this study consisted of 148 companies in retail trade, service and investment group that were listed on the Indonesia Stock Exchange. The sample chosen by purposive sampling was chosen to be 17 companies listed on Indonesia Stock Exchange during 2014 to 2017. Data collection techniques used were documentation techniques. Data processing technique used is data processing with SPSS version 21. Data analysis method used is multiple linear regression method. Results of the T test show that partially Current Ratio, Debt to Asset Ratio, and inventory turnover have a negative and significant effect on company performance, while Return On Investment has a positive and significant influence on company performance. The results of the F test analysis indicate that the variable Liquidity Ratio, Profitability, Solvability and Inventory Turnover together have a significant effect on company performance.